Impact of Feed Presentation Form and Feeding Strategy on Egg Quality - SEIBOU TOLEBA, Soumanou (My University, 2022)
Egg production in Benin is subject to a several constraints that hinder its development despite the growing demand for animal proteins. Therefore, finding innovative means and techniques to guarantee quality and quantity of production would be advantageous. The aim of this work is to determine the influence of animal feed supplements on egg quality. A total of 144 Isa Brown laying hens randomly to six (6) groups and four (4) replicates with six (6) hens per group (for each feed treatment) formed the experimental design. The hens were housed in ventilated and lighted cages and the experiment lasted five (5) months of laying. Six (06) feed treatments were tested: ACF (Mealy completed food), ACG (Granular completed food), CGMc (Granular supplements mixed with cracked maize), Mc+CF (Cracked maize morning / Mealy supplement at 1:00 p.m.), CF+Mc (Mealy supplement morning / Cracked maize at 01:00 p.m.) and CG+Mc (Granular supplement morning / Cracked maize at 01:00 p.m.). The external and internal physical quality of the eggs was determined. The form of presentation and the mode of distribution significantly influenced the physical quality of the eggs (p < 0.05). ACF and CGMc showed good shell strength (7.80 ± 0.28; 7.70 ± 0.28). The Mc+CF treatment accumulated the best external and internal physical quality scores. This treatment would be recommended to poultry farmers to have eggs with the best quality.
Keywords: Food Supplement; Maize; Granular; Mealy; Sequential Distribution